Assessing the Contemporary Issues of Countering Transnational Crime - Ivan Kubariev; Yevgen Barash; Valeriy Pcholkin; Olena Pluzhnik (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
Crimes are always considered as inevitable in every given society operating under an organized system of operation. Sometimes this crime has to cross borders constituting huge threat to country sovereignty and integrity. With all this in place, States are usually confronted in establishing possible forms and methods of combating the so called transnational crimes. Specific examples of successful experience of developed countries, such as the United States, Canada and Western European countries, are analyzed. The author's definitions of the terms